THE Design of Fire Fighting Sprinkler System by Autodesk Revit - Santha kumar, Kugkan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This study is about active firefighting sprinkler system. Overall view of a firefighting system has been studied. As a summary, firefighting systems has been classified into two categories, which is active firefighting and passive firefighting. Active firefighting is a group that require some amount of action or motion in order to work, it is divided to manual system and automatic system. Passive firefighting are known as building materials that are always present and available within the building, placed and located evenly every floors of the building. Besides that, the standards and codes for firefighting system has been studied, the standard which is needed to follow is NFPA 13 and UBBL 1984. While planning to design a fire sprinkler system, there is few major factors which are need to be considered. The first one is the type of sprinkler system according to the nature of building, the second one is the type of sprinkler head and lastly the regulations which is standardized by the government. The digital designing project is carried out using Autodesk Revit . After the research and study process, the sprinkler system for a light hazard category building was designed in comply following the standard of NFPA 13, the upright sprinkler head which covers 225 square feet per sprinkler is used. As the outcome for the requirement, a double storey clinic and the sprinkler system with the single chamber valve and storage tank was design using Autodesk Revit.